Recurrence of LV Thrombus in a Patient with Severe Ischaemic Cardiomyopathy Anticoagulated with Apixaban. (21st July 2022) - Farooqui, Azhar; Lwin, Tin; Costa, Daniel; Hetherington, Simon; Mattu, Raj
Abstract : Background . Anticoagulation with warfarin remains the mainstay treatment for left ventricular thrombi. Although successful thrombus resolution has been reported with direct oral anticoagulants' (DOACs') recurrence/progression while resuming Apixaban therapy is yet to be reported. Case Presentation . This case report describes left ventricular thrombus progression/recurrence in a patient anticoagulated with Apixaban undergoing implantable cardioverter defibrillator to cardiac resynchronisation therapy with defibrillator upgrade procedure. He was thereafter changed to warfarin. Contrast echocardiogram at 6 months follow-up did not identify the previously demonstrated mural thrombus. Conclusion . Prospective randomised control trials should be conducted in patients with left ventricular thrombus to compare anticoagulants, assess the efficacy and safety of DOACs, and evaluate uninterrupted DOAC versus transient withdrawal for cardiac device procedures.